Fracture prevalence of dental crown primary anterior teeth on early childhood education students - Miryasandra, Astari; Sasmita, Inne Suherna; Hidayat, Syarief (Faculty of Dentistry Universitas Padjadjaran, 2014)
Introduction: Teeth injury is a pathological changes in dental hard tissues of the teeth with or without accompanied by damage to surrounding tissue. There are various kinds of trauma to the teeth, one of them is crown fractures. Primary anterior teeth crown fractures is common in children. The aim was to obtain the prevalence of primary anterior teeth crown fractures. Methods: The research was a descriptive study with survey technique. The samples were chosen by cluster random sampling technique. The samples were 315 children who enroll in Early Childhood Education Institution in Cimahi consisting of 139 boys and 176 girls. The prevalence was counted by dividing the numbers of Early Childhood Education students who suffered from crown fracutres with the total numbers of Early Childhood Education students at Cimahi and multiply by a hundred percent. Result: Prevalence of primary anterior teeth crown fractures in Early Childhood Education students in Cimahi is 5.1%. Conclusion: Prevalence of primary anterior teeth crown fractures in Early Childhood Education students in Cimahi is less than a quarter of the total samples.